The economic costs and consequences of terrorism - Richardson, Harry Ward; Gordon, Peter 1943-; Moore, James Elliott (E. Elgar, 2007)
This landmark book covers a range of issues concerning the consequences of terrorist attacks. Beginning with a discussion of new policies and strategies, it then delves into specific areas of concern, modeling a range of possible scenarios and ways to mitigate or pre-empt damages. Top researchers from around the world discuss issues such as: airport security, urban terrorism, Coast Guard operations, and the need to balance freedoms with security. New policies for deterring terrorism are also proposed. Later chapters model the economic impacts of terrorist attacks on the food industry, major US ports, and US theme parks. The final chapters provide an in-depth look at the effects of interruptions to electricity supply and how to improve resiliency. Using specific locations and situations, the volume details in a concrete way the long and short-term economic effects of possible future attacks. The cutting-edge research and provocative conclusions make this a must-read for policymakers, public sector economists, urban planners, aviation officials, insurance industry analysts and those charged with disaster management.